2021
DOI: 10.1128/msystems.00702-21
|View full text |Cite
|
Sign up to set email alerts
|

Plasmids Shape the Current Prevalence of tmexCD1-toprJ1 among Klebsiella pneumoniae in Food Production Chains

Abstract: Tigecycline, the first member of the glycylcycline class of antibacterial agents, is frequently used to treat complicated infections caused by multidrug-resistant Gram-positive and Gram-negative bacteria. The emergence of a novel plasmid-mediated efflux pump, TmexCD1-ToprJ1, conferring resistance to multiple antimicrobials, including tigecycline, poses a huge risk to human health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…in food production chains according to the host range analysis and seemed to be primary vectors for the horizontal dissemination of tmexCD1 - toprJ1 among Klebsiella spp. ( Peng et al., 2021 ). Notably, IncFIB(Mar)/IncHI1B-type plasmid carrying tmexCD1 - toprJ1 gene could not conjugate to E. coli J53 and E. coli C600 strains but could be transformed to E. coli DH5α strains by electroporation ( Peng et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…in food production chains according to the host range analysis and seemed to be primary vectors for the horizontal dissemination of tmexCD1 - toprJ1 among Klebsiella spp. ( Peng et al., 2021 ). Notably, IncFIB(Mar)/IncHI1B-type plasmid carrying tmexCD1 - toprJ1 gene could not conjugate to E. coli J53 and E. coli C600 strains but could be transformed to E. coli DH5α strains by electroporation ( Peng et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…( Peng et al., 2021 ). Notably, IncFIB(Mar)/IncHI1B-type plasmid carrying tmexCD1 - toprJ1 gene could not conjugate to E. coli J53 and E. coli C600 strains but could be transformed to E. coli DH5α strains by electroporation ( Peng et al., 2021 ). However, the two plasmids in this study could not be transferred to recipient E. coli strains by either conjugation or transformation with E. coli strains, indicating that this IncFIB(Mar)-like/IncHI1B-like type plasmids might be more restricted by the host species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic context analysis revealed that tmexCD-toprJ was positioned in a conserved mobile unit with genetic arrangement int - int - hp - hp - tnfxB - tmexCD - toprJ in the two plasmids. Previous studies have uncovered that similar mobile units containing tmexCD-toprJ were present in many strains ( 23 , 24 ). As yet, no studies have been conducted to demonstrate the mobility such mobile units.…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, different variants of tmexCD-toprJ shared a similar genetic structure ( 14 , 15 , 25 ), implying that these tmexCD-toprJ variants originated from a common ancestor and then propagated to different bacteria. It should be noted that IS 26 -mediated movement of tmexCD-toprJ has been detected in many strains ( 24 , 26 ), and we should therefore present an effective way to prevent further dissemination of tmexCD-toprJ . Apart from tmexCD-toprJ , bla IMP-4 and bla NDM-1 were also located in mobile elements.…”
Section: Discussionmentioning
confidence: 99%